Review of the Flexible Credit Line, the Precautionary and Liquidity Line, and the Rapid Financing Instrument : Specific Proposals. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
This annex provides the key considerations for establishing the qualification framework to access financing under the FCL and PLL, with a view to promoting a predictable and evenhanded qualification process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Annex I. FCL; FCL Arrangement; GDP; PLL; PP